‘Never an It’: Intersubjectivity and the creation of animal personhood in animal shelters - Taylor, Nicola (Qualitative Sociology Review, 2007)
This paper argues that sociology should begin to turn its attention to human-animal interaction and that one particularly effective way to do so is to adopt a phenomenological approach. This approach sees the personality, and thus the personhood of animals, as intersubjectively and reflexively created. Based on ethnographic data collected over three years in animal sanctuaries this paper assesses how animal sanctuary workers labour collectively to establish the identity of the animals under their care and how this, in turn, justifies their attitudes towards, and treatment of, them.